If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -35 + -2x = 13 + -10 Combine like terms: 13 + -10 = 3 -35 + -2x = 3 Solving -35 + -2x = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '35' to each side of the equation. -35 + 35 + -2x = 3 + 35 Combine like terms: -35 + 35 = 0 0 + -2x = 3 + 35 -2x = 3 + 35 Combine like terms: 3 + 35 = 38 -2x = 38 Divide each side by '-2'. x = -19 Simplifying x = -19
| 2x=3(1-x) | | 2x+36=12-74 | | (x+3y-5z)-(x-2y+6z)= | | x^2+4x^2=16 | | x-6y=-29 | | x=x^2-0.25 | | 4n-12=n-27 | | .55(F-32)=25 | | 0.125n+0.75=-0.125n-0.25 | | -6+8(x-3)=12x+6-4x | | (2x-3)-(2x-3)(x+1)-2(2x-3)=0 | | 5x+18=5x+15 | | (5-x)(2x+1)=18x | | -x-5y=-37 | | 9b=-72 | | 347.06=200+0.57x | | 20000=(x*.2)+x | | -3(5x+7)=-21 | | 7(1x+6)=28 | | 4*(n*-3)=n-27 | | 3(-r)+5= | | c^8-15625c^2=0 | | 12.0x+10=34+9.9x | | a^6+32a=0 | | c+c*c=0.24 | | 3x^6-x^3-24=0 | | 3x^2+3=x | | 59-4x=14x+19 | | 3w+(3w+36)=84 | | 9x^2y^2+9xy+2= | | 5x-10=98+6x | | x^2y^2-3xy+2=0 |